2016
DOI: 10.1504/ijmr.2016.076976
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on core drilling by ultrasonic-vibration-assisted grinding for hard-to-machine materials - a review

Abstract: Ultrasonic-vibration-assisted grinding (UVAG), a hybrid machining process combining material removal mechanisms of diamond grinding and ultrasonic machining, has been used to machine various hard-to-machine materials. Large amount of research work on UVAG has been carried out since it is invented. However there are few review papers to cover the current literature on UVAG. The emphasis of this literature review is the experimental investigations of the drilling process with ultrasonic vibration using a core dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…10 Ultrasonic vibration-assisted machining is a special machining method that makes the tool or the workpiece produce highfrequency vibration to realize the intermittent cutting of the workpiece, and it could reduce cutting force and improve surface quality. [11][12][13] Gao et al [14][15] conducted milling and drilling tests on Ti-6Al-4V alloy using UVAM, and the results showed that UVAM can significantly reduce the cutting force and inhibit the generation of burrs. Many scholars have done a lot of research on the application of UVAM in the machining of SiCp/Al composites.…”
Section: Introductionmentioning
confidence: 99%
“…10 Ultrasonic vibration-assisted machining is a special machining method that makes the tool or the workpiece produce highfrequency vibration to realize the intermittent cutting of the workpiece, and it could reduce cutting force and improve surface quality. [11][12][13] Gao et al [14][15] conducted milling and drilling tests on Ti-6Al-4V alloy using UVAM, and the results showed that UVAM can significantly reduce the cutting force and inhibit the generation of burrs. Many scholars have done a lot of research on the application of UVAM in the machining of SiCp/Al composites.…”
Section: Introductionmentioning
confidence: 99%